Implantação de sistema de gestão ambiental ISO 14000: proposta de metodologia para indústrias de fertilizantes - Cipolat, Carina (2003)
One of the biggest challenges of chemical industries of fertilizer sector is on the search to attend the ambiental requirements, aiming guarante the conformity with all legal requirements and community too. The search for the reduction of wastefulnesses, as well as the prevention and the reduction of the pollution and the industrial residues is part of these company day-by-day. Since problems related to environment are a permanent concern, due to the chemical activities performed and present in this sector. This work main objective consists on the elaboration of a methodology for the implantation of an ambiental management system at fertilizer industries. The model was elaborated based on studies of cases done at Bunge Fertilizing S/A productive units, verifyng the carriage of all the ambiental management implantation stages at the selected units, verifying its advantages, disadvantages, improvements, aspects, ambiental impacts inherent to the processes and difficults found in the implantation as well. To compose the theoretical base was performed a bibliographical research approaching the evolution of fertilizer chemical industry in the country, its importance inside the Brazilian market and the relation to the environment. For data collection releated to the study of performed case, were performed documental and direct surveys releated with utilization of field research, as well as intensive direct observation through interviews and comments.. Through this boarding the methodology development for environmental management systems (EMS) implantation was possible, according to the requirements of ISO 14001, capable to save the fertilizer chemical industries.